Computer identification of Notch3 in the neurogenic progenitor cells of mammalian early optic vesicles - Yoshitoku Watabe; Sakurako Kobayashi; Satoru Takahashi; Masaharu Yoshihara (BMC Research Notes)
Abstract Objective The developing mammalian retina initially contains undifferentiated cells, providing a model for investigating the mechanisms of differentiation. Notch signaling, mediated by four Notch receptors (Notch 1–4) in mammals, has been studied in the differentiation of neural progenitor cells. Among the four Notch receptors, the frequency, rather than the peak level, of Notch1-mediated signaling has been suggested to promote the activation of neural progenitor cells. In contrast to Notch1, the involvement of Notch3 in this process is poorly documented, although Notch3 is known for its role in vascular integrity. Results By re-analyzing publicly available single-cell RNA-seq data from one mouse retinal dataset, two human retinal organoid datasets and two human embryonic retinal datasets, we found that, along with Notch1, Notch3 is expressed in neural progenitor cells in the retina. In addition, the results of the co-expression profile analyses varied among the datasets, leaving uncertainty regarding the regulatory mechanisms of Notch1 and Notch3. Our findings shed light on Notch3 in neurogenic progenitor cells of the developing mammalian retina. Since Notch3 has been suggested to cause ligand-independent signaling, Notch3 expression might antagonize Notch1-mediated signaling oscillations, maintaining the quiescent state of neurogenic progenitor cells.